Penerapan konseling kelompok dalam mengatasi kecemasan akademik siswa - rachmad, haidar masbubir (Maliki Interdisciplinary Journal, 2025)
Academic anxiety is a common psychological problem experienced by students in secondary education. Pressure to achieve, parental demands, and competition among students are all triggers for anxiety, which can impact concentration, learning motivation, and even academic achievement. One effective approach to addressing academic anxiety is group counseling. In group counseling, students can share experiences, receive social support, and learn strategies for managing anxiety more healthily. This article discusses the application of group counseling to address students’ academic anxiety, focusing on the implementation stages, benefits, and a simple case study example in a school setting. The study results indicate that group counseling can have a positive impact on reducing academic anxiety and increasing students’ readiness to face learning challenges.